LoRa Communication in the Service Level Monitoring Satu Duit Bogor Bridge - Setiowati, Sulis; Riandini, Riandini; Sari, Via Arsita; Purwanti, Indah Luthfiyyah; Andriansyah, Noval (Universitas Andalas, 2023)
Lora is the solution to the problem of the need for long-distance two-way communication between machines that are targeted by IoT (Internet of Thins. LoRa has long-distance transmission capabilities, has power, and a low bit rate. Based on the needs related to LoRa, further research is needed, to analyze the performance of LoRa communication. The LoRa communication protocol will be applied to the One Duit Bogor bridge monitoring system using the Website and LabVIEW. This study used LoRa SX1276 with a frequency of 915MHz with the LoRa point-to-point method and LoRa gateway. The parameters analyzed include RSSI (Received Signal Strength Indicator), SNR (Signal to Noise Ratio), Delay, Throughput, and Packet loss to determine the quality of LoRa performance with TIPHON standards. Based on the tests that have been carried out, it proves that LoRa communication has good performance. In urban areas or around the Satu Duit Bogor bridge, LoRa can transmit data from a distance of 0 to 500 m with an average delay of 217 ms, an average packet loss of 10.237%, an average throughput of 137.881 bps, an average SNR of 7.54 dB, and an average RSSI of -71,798 dBm. At a distance of 0-400 m there is an insignificant change in LoRa parameters, but at a distance of 500 m a high change occurs, this is due to the fact that the distance greatly affects the transmission of data. The longer the range, the more obstacles will be passed so that data transmission is disrupted.